Effects of c-Jun N-terminal kinase on Activin A/Smads signaling in PC12 cell suffered from oxygen-glucose deprivation - Wang, J Q; Xu, Z H; Liang, W Z; He, J T; Cui, Y; Liu, H Y; Xue, L X; Shi, W; Shao, Y K; Mang, J; Xu, Z X (Cellular and Molecular Biology, 2016)
Activin A (Act A), a member of transforming growth factor-Î² (TGF-Î²) superfamily, is an early gene in response to cerebral ischemia. Growing evidences confirm the neuroprotective effect of Act A in ischemic injury through Act A/Smads signal activation. In this process, regulation networks are involved in modulating the outcomes of Smads signaling. Among these regulators, crosstalk between c-Jun N-terminal kinase (JNK) and Smads signaling has been found in the TGF-Î² induced epithelial-mesenchymal transition. However, in neural ischemia, the speculative regulation between JNK and Act A/Smads signaling pathways has not been clarified. To explore this issue, an Oxygen Glucose Deprivation (OGD) model was introduced to nerve-like PC12 cells. We found that JNK signal activation occurred at the early time of OGD injury (1 h). Act A administration suppressed JNK phosphorylation. In addition, JNK inhibition could elevate the strength of Smads signaling and attenuate neural apoptosis after OGD injury. Our results indicated a negative regulation effect of JNK on Smads signaling in ischemic injury. Taken together, JNK, as a critical site for neural apoptosis and negative regulator for Act A/Smads signaling, was presumed to be a molecular therapeutic target for ischemia.